(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the role and significance of artistic literature in developing aesthetic taste within directing education. It examines, from both theoretical and practical perspectives, how literary works contribute to the moral and ethical worldview, emotional perception, and creative thinking of young directors. The study also highlights pedagogical methods that enhance the ability to analyze literary texts, develop figurative thinking, and use literary sources effectively in the process of staging performances.